Object oriented XSLT a new paradigm for content management. - Michelucci, Pietro (XML journal :the ultimate enterprise resource.)
What could be better for managing content than separating data from presentation? How about separating data from data? Believe it or not. XSLT can actually be used to allow for different levels of data abstraction. In practical terms, this can reduce the complexity of managing Web content by an order of magnitude and facilitate code reuse. In essence, what I'm talking about here is object-oriented XSLT, or to add to the alphabet soup: OOX (pronounced ooks).